Additional file 8 of Comparative genomics of the coconut crab and other decapod crustaceans: exploring the molecular basis of terrestrial adaptation - Werner Pieter Veldsman (10733028); Ka Yan Ma (9348645); Jerome Ho Lam Hui (10733031); Ting Fung Chan (8826122); J. Antonio Baeza (9012707); Jing Qin (41397); Ka Hou Chu (10274112) (2021)
Additional file 8: Figure S1. Heatmaps of the most highly alternatively spliced genes per tissue type. Alternative splicing profiles of genes with known gene symbols (top) as well as genes without known gene symbols (bottom) for (A) Birgus latro, (B) Paralithodes camtschaticus (C) Panulirus ornatus (D) Litopenaeus vannamei. The wupA gene is noteworthy due to it being spliced in all species except Panulirus ornatus. These heatmaps were drawn with RStudio version 1.1.456 [69] (with R base packages) and Microsoft PowerPoint.